2008
DOI: 10.1111/j.1742-481x.2008.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitin membrane for wound dressing application – preparation, characterisation and toxicological evaluation

Abstract: Chitin, a unique biopolymer based on the N-acetyl-glucosamine monomer is envisioned to promote rapid dermal regeneration and accelerate wound healing. It has many useful and advantageous biological properties for its application as a wound dressing. Chitin membranes were prepared using lithium chloride/dimethylacetamide solvent system and evaluated for use as a wound dressing. Swelling behaviour, moisture vapour transmission rate, microbial impermeability and antimicrobial efficacy of the dressings was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Table 3 shows commercial antibacterial wound dressing materials containing these bioactive materials 61. Recent developments in wound dressing materials and their production methods as well as the ingredients used have been reviewed 62–75…”
Section: Wound Dressings and Their Propertiesmentioning
confidence: 99%
“…Table 3 shows commercial antibacterial wound dressing materials containing these bioactive materials 61. Recent developments in wound dressing materials and their production methods as well as the ingredients used have been reviewed 62–75…”
Section: Wound Dressings and Their Propertiesmentioning
confidence: 99%
“…Marine-origin materials are frequently proposed for many biomedical applications. As examples, collagen [22], chitin [23] and chitosan [24] were reported as candidates for the development of wound dressings. However, to the best of our knowledge, no report has previously proposed FSP for this biomedical application.…”
Section: Introductionmentioning
confidence: 99%
“…21 Macromolecules most exhaustively studied are cellulosic derivatives, with ethylcellulose (EC) being the one with the highest functionality. [28][29][30][31][32][33][34][35] Chitin organogels with common edible lipid material (oils), could also be used as an alternative for solid fat in many food-products or food-related applications. 21, 24 Sanchez and co-workers showed that EC can be used to create organogels and that by changing the molecular weight of the polymer, the mechanical properties of the organogel could be altered.…”
Section: Introductionmentioning
confidence: 99%